2017
DOI: 10.1002/ajpa.23226
|View full text |Cite
|
Sign up to set email alerts
|

Dental wear and age grading at Roonka, South Australia

Abstract: The pattern of wear is consistent with ethnographic observations, which suggest a degree of latitude in the activities of juveniles and young adults. By middle age variability between individuals declines reflecting shared tasks and more intensive use of the teeth. The pattern of wear amongst old adults, however, is much flatter presumably due to changes in occlusion. While dental wear is informative about the organization of labor there is a need to take into account both patterns of activity and occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Specifically, previous studies have shown that the extent of dental wear is strongly correlated with chronological age, regardless of time periods or geographical locations (e.g., Dreier, 1994;Littleton, 2017;Lovejoy, 1985;Mays & Pett, 2014;Molnar, Mckee, Molnar, & Przybeck, 1983;Richards & Brown, 1981;Richards & Miller, 1991;Takei, 1970;Tomenchuk & Mayhall, 1979). Dental wear is widely accepted as a physiological consequence of aging, and the evaluation of dental wear can be a simple tool with which to estimate the age of an adult (Kim et al, 2000;Li & Ji, 1995).…”
mentioning
confidence: 99%
“…Specifically, previous studies have shown that the extent of dental wear is strongly correlated with chronological age, regardless of time periods or geographical locations (e.g., Dreier, 1994;Littleton, 2017;Lovejoy, 1985;Mays & Pett, 2014;Molnar, Mckee, Molnar, & Przybeck, 1983;Richards & Brown, 1981;Richards & Miller, 1991;Takei, 1970;Tomenchuk & Mayhall, 1979). Dental wear is widely accepted as a physiological consequence of aging, and the evaluation of dental wear can be a simple tool with which to estimate the age of an adult (Kim et al, 2000;Li & Ji, 1995).…”
mentioning
confidence: 99%
“…Wear on the anterior teeth is frequently greater or equivalent to the first molar, reflecting the use of the teeth for nonmasticatory purposes. This pattern of wear reflects age graded acquisition of tasks (Littleton, ) but shows very little difference between males and females.…”
Section: Discussionmentioning
confidence: 87%
“…Carbon and nitrogen stable isotope analysis of collagen by Pate () does not show evidence of significant sex differences suggesting a similar intake of animal protein sources. Comparably the dental wear analysis (Littleton, ) suggests a lack of difference in abrasiveness (which was probably high for both males and females). One cannot assume from this, however, that there was an absence of a gender division in food since our indicators are partial and time averaged.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, Littleton, Scott, Mcfarlane, and Walshe (2013) demonstrate that the use of population averages in analysing dental macrowear can obscure significant differences between individuals. Indeed, analyses of dental wear by age and sex show marked intra-group variability, but notably also that the specific patterns of age-and sex-related wear change by location (see Littleton, 2017;Littleton, Scott, Mcfarlane, & Walshe, 2013;Richards, 1984;Smith, Prokopec, & Pretty, 1988). So even when dental wear is uniformly severe, its patterning reflects not just ecological zones and the available resources but also differences in economic organisation between those zones.…”
Section: Dietary Analysesmentioning
confidence: 99%